Fraudulent financial reporting in public companies in Indonesia: An analysis of fraud triangle and responsibilities of auditors - Sri Astuti; Zuhrohtun Zuhrohtun; Kusharyanti Kusharyanti (Universitas Hayam Wuruk Perbanas, 2015)
This study investigates the determinants of fraudulent financial reporting in Indonesia and the responsibility of auditor for fraudulent financial reporting. This study posits that fraud triangle affects the fraudulent financial reporting, and auditors do not give unqualified opinion for fraud firms. The sample consists of 380 firms listed on Indonesia Stock Exchange. The 39 of 380 firms have received punishment from BAPEPAM during 2007-2010 periods. This study uses logistic regression to test the first hypothesis and correlation to test the second hypothesis. The finding suggests that: 1) fraud triangle (opportunity, pressure, and rationalization) does not affect the fraudulent financial reporting; 2) auditor opinion has a positive correlation towards fraudulent financial reporting.